Students’ Learning Style in Learning Vocabulary at the Eleventh Grade of Senior High School 3 Jambi City - Muhammad Imam Julianto; Wennyta Wennyta; Kartika Dewi (Universitas Batanghari Jambi, 2022)
This research was aimed to find out what are the learning style used by the students at the Eleventh Grade of Senior High School 3 Jambi City. The research methodology of this study was quantitative descriptive research which involved population and sample. The total population of this research was the XI MIPA 1 students of Senior High School 3 Jambi City, which consisted of 28 students. In collecting the data, This research gave questionner as the instrument to collect the data at the class. The result of the research showed that the eleventh grade students of Senior High School 3 Jambi City learn English vocabulary in various ways. Moreover, the students with the highest percentage was found in auditory learning style (43%), then followed by visual learning style (21%), and the last kinesthetic learning style (21%). This research also found some students with multiple learning style which is visual/kinesthetic learning style (11%) and auditory/kinesthetic learning style (4%). This research concluded that students have different learning style in learning English, and they have a different way of developing their English skills in learning.